EARLY DIAGNOSTICS OF HEART FAILURE IN PATIENTS WITH CORONARY HEART DISEASE - O. V. Bulashova; A. I. Abdrakhmanova (Российский кардиологический журнал)
A screening of chronic heart failure (CHF) in patients with Coronary Heart Disease (CHD) has been done. An echocardiography study (echo) was used to reveal possible variants of left ventricle myocardium dysfunction. A group of patients with left ventricle diastolic dysfunction (LVDD) was selected. After a meticulous clinical examination including stress tests the diagnosis of CHF has been made in 85.9 % patients. An attempt has been made to determine most diagnostically valuable echo parameters characterizing left ventricle relaxation function in various CHF functional classes in coronary patients. Therefore the presence of normal contractile function of left ventricle myocardium probably does not rule out the presence of CHF in patients with long term CHD. Patient assessments must include evaluation of LV diastolic function with subsequent physical stress tests for final decision on the presence of CHF.